Broth & stock from the Nourished kitchen : wholesome master recipes for bone, vegetable, and seafood broths and meals to make with them - McGruther, Jennifer (Ten Speed Press, 2016)
"A cookbook from the author of the popular website The Nourished Kitchen, featuring 60 recipes for nutritious and healthy master broths, soups, stews, gravies and other dishes using poultry, meat, vegetable, and seafood broths. Nutrient-dense bone broths are having a major moment: from the $8 per cup servings at New York "broth bars" to Kobe Bryant crediting its restorative properties for his improved athletic performance, broths are in the news and being turned to for their health properties. Jennifer McGruther is the perfect author to address this topic--a trusted authority on traditional foods who has been touting the value of broth since before it was trendy. The health benefits of broth are many: it is rich in protein, calcium, magnesium, phosphorus, and other trace minerals, which are easily absorbed by the body when consumed in liquid form. Bone broth has been proven to help mitigate the effects of arthritis and joint pain since it contains glucosamine, gelatin, collage, and chondroitin. Broth and Stock from the Nourished Kitchen features recipes for the broths themselves as well as soups, stews, and meat dishes that incorporate broths, and is the ideal guide for anyone interested in integrating these healthful concoctions into their daily lives simply and approachably"--